Jenis-Jenis Reptilia di PPKA Bodogol, Taman Nasional Gunung Gede Pangrango - Yuniar, Debby; Isfaeni, Hanum; Sukandar, Paskal; Noer, Mohamad Isnin (LPPM Universitas Negeri Jakarta, 2014)
Abstract Ecological studies of reptiles in Java were rarely executed during the last decade, because many scientist have focused exclusively on taxonomical studies. Also, studies about diversity of reptiles which have been heretofore published mostly incorporated with amphibians, and nearly all of those studies concerning in unravel the diversity of amphibians. In Bodogol, Gede- Pangrango National Park, survey about reptiles diversity have been done frequently, but just few researches that have been published and most of all were short term research studies. Hence, a research that concern in studying diversity of reptiles become valuable to carry out. Herein, we studied the diversity of reptiles in Bodogol during November 2011 to March 2012. Reptiles’ species were collected by searching in available trail other than Tangkil, Cipanyairan I, and Cipanyairan II. Total of twenty three species of reptiles were found, encompassing six families (Colubridae, Elapidae, Viperidae, Scincidae, Agamidae, and Gekkonidae). Number species of reptiles occured in Bodogol were quite similar to other largest nature reserve areas within the same geographic range (e.g. Halimun-Salak and Ujung Kulon National Park). Despite its small in size, Bodogol contains various types of habitat which therefore could support a variety species of reptiles. Key words : bodogol, diversity, reptiles, java